Lasswell Communication Model to Improve Students' Mathematical Concepts Understanding Ability - Lena, Mai Sri; Netriwati, Netriwati; Suryanita, Ika; Khairat, Fastabuqul; Efendi, Ulfah Putri (International Journal on Emerging Mathematics Education, 2022)
This research aimed to discover the difference in the increase of students' mathematical concepts understanding using Lasswell communication model and conventional model. This was quasi-experimental research. Data were collected through a test of mathematical concepts understanding. The sample of this research was Public High School 4, where class X.1 and class X. 2 as an experiment and control class respectively. Inferential statistics was used to analyze the data. The findings showed that the increase of average of students' mathematical concepts understanding ability of experimental class was 0.733, while in the control class was 0.550. Furthermore, the results of the analysis of the t-test with significance level were 5%, showed that t score>T-table, meaning H0 was rejected. The conclusion was that there was a difference in the increment of students' mathematical concepts understanding using Lasswell Communication model and conventional model. Therefore, increasing the students' ability of mathematical concepts understanding using the Lasswell Communication Model was better than the conventional model.